A literature synthesis of personalised technology-enhanced learning: what works and why - FitzGerald, Elizabeth; Jones, Ann; Kucirkova, Natalia; Scanlon, Eileen (Research in Learning Technology, 2018)
Personalised learning, having seen both surges and declines in popularity over the past few decades, is once again enjoying a resurgence. Examples include digital resources tailored to a particular learner’s needs, or individual feedback on a student’s assessed work. In addition, personalised technology-enhanced learning (TEL) now seems to be attracting interest from philanthropists and venture capitalists indicating a new level of enthusiasm for the area and a potential growth industry. However, these industries may be driven by profit rather than pedagogy, and hence it is vital these new developments are informed by relevant, evidence-based research. For many people, personalised learning is an ambiguous and even loaded term that promises much but does not always deliver. This paper provides an in-depth and critical review and synthesis of how personalisation has been represented in the literature since 2000, with a particular focus on TEL. We examine the reasons why personalised learning can be beneficial and examine how TEL can contribute to this. We also unpack how personalisation can contribute to more effective learning. Lastly, we examine the limitations of personalised learning and discuss the potential impacts on wider stakeholders.

Tablet use in schools: a critical review of the evidence for learning outcomes - Haßler, Björn; Major, Louis; Hennessy, Sara (Journal of Computer Assisted Learning, 2016)
Keywords: Android; Author:Haßler; dode_eth-src-dode; dode_eth-trf2-dode; iPad; learning outcomes; school; systematic reviews; tablets

Keyword inventory (version 1) - Haßler, Björn; Adam, Taskeen; Brugha, Meaghan; Damani, Kalifa; Allier-Gagneur, Zoe; Hennessy, Sara; Hollow, David; Jordan, Katy; Martin, Kevin; Murphy, Mary; Walker, Hannah (EdTech Hub, 2019)
The document contains the keyword inventory used for automated searching. This file is now superseeded by DOI: 10.5281/zenodo.3908363, see https://docs.edtechhub.org/lib/55A44ZRB.
Keywords: _DOILIVE; _EdTechHub_Output; _MELA_seen; _cover:analysis:nopdf; _yl:p; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode